Triglyceride-Glucose Index for the Diagnosis of Metabolic Syndrome: A Cross-Sectional Study of 298, 652 Individuals Receiving a Health Check-Up in China. (29th June 2022) - Jiang, Mingfei; Li, Xiaoran; Wu, Huan; Su, Fan; Cao, Lei; Ren, Xia; Hu, Jian; Tatenda, Grace; Cheng, Mingjia; Wen, Yufeng
Abstract : Objective . We herein aim to explore the relationship between the triglyceride-glucose (TyG) index and metabolic syndrome (MS). Methods . We enrolled 298, 652 individuals with an average age of 47.08 ± 12.94 years and who underwent health check-ups at the First Affiliated Hospital of Wuhu Wannan Medical College in this cross-sectional study from 2014 to 2016. We enlisted 125, 025 women (41.86%) and 173, 627 men (58.14%). The survey information included a questionnaire survey, a physical examination, and a laboratory examination. Results . The prevalence of MS increased gradually in the TyG-index subgroups ( Q 1, TyG <8.30; Q 2, 8.30≤ TyG <8.83; and Q 3, TyG ≥8.83). We noted significant differences in hypertension, hyperlipidemia, hyperglycemia, sex, age, body mass index (BMI), smoking and drinking habits, and estimated glomerular filtration rate between the TyG-index subgroups. Multiclass logistic regression analysis showed that the group with TyG <8.30 was the reference group, and the 8.30≤ TyG <8.83 and the TyG ≥8.83 groups exhibited a higher TyG index with MS, and a lower TyG index without MS disease. In the linear curve analysis of the TyG index and MS components, BMI, systolic blood pressure, and diastolic blood pressure showed upward trends, while high-density lipoprotein cholesterol showed no obvious trend in the TyG index at a range of 7.8–11.0. Receiver operating characteristic analysis was used to evaluate the predictive value of the TyG index, triglycerides, and fasting blood glucose for MS, and we found that the area under the TyG index curve was the largest (AUC = 0.89). Conclusion . There were associations between the TyG index and MS and its components, and the TyG index is therefore of great value in the early diagnosis of MS.